2013
DOI: 10.1371/journal.pone.0075062
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Serotonin, Tryptophan Hydroxylase and Monoamine Oxidase A in the Mammary Gland of the Myotis velifer Bat

Abstract: The mammary gland has long drawn the attention of the scientific community due to the limited knowledge of some fundamental aspects involved in the control of its function. Myotis velifer, a microchiropteran species, provides an interesting model to study some of the regulatory factors involved in the control of the mammary gland cycle. Having an asynchronous, monoestrous reproductive pattern, female M. velifer bats undergo drastic morphological changes of the breast during the reproductive cycle. Current rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In mammals, a few studies have reported the presence and distribution of 5-HT in reproductive organs from both male and female individuals, but its functional contributions remain obscure (Fujinoki, 2011;Jiménez-Trejo et al, 2012, 2013Vela-Hinojosa et al, 2013). In a first attempt to decipher its role, we have described the distribution of several elements of the serotoninergic system in the testes during spermatogenesis, the mating period, fertilization, and the sperm maturation processes occurring in the caput epididymis (Jiménez-Trejo et al, 2007, 2012, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, a few studies have reported the presence and distribution of 5-HT in reproductive organs from both male and female individuals, but its functional contributions remain obscure (Fujinoki, 2011;Jiménez-Trejo et al, 2012, 2013Vela-Hinojosa et al, 2013). In a first attempt to decipher its role, we have described the distribution of several elements of the serotoninergic system in the testes during spermatogenesis, the mating period, fertilization, and the sperm maturation processes occurring in the caput epididymis (Jiménez-Trejo et al, 2007, 2012, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In an autocrine-paracrine fashion, serotonin is known to regulate tight junctions between mammary epithelial cells to control milk volume 9 and β-casein expression 10 , specifically through the serotonin receptor 7 11 in mouse and human epithelial cells. Serotonergic regulation appears to be conserved across species: the bovine mammary gland is known to express several serotonin receptor isoforms 12 and the Myotis velifer bat mammary gland shows differential expression of serotonin and Tph 13 . Serotonin has also been implicated in the regulation of a variety of broader physiological processes during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…19) Although we did not determine levels of the 5-HT7 receptor or occurrence of apoptosis in this study, the decrease in β-casein protein upon 5-HT treatment is likely induced via signaling through the 5-HT7 receptor, accompanied by apoptosis. Furthermore, a 5-HT transporter has been detected in human mammary epithelial cells, 20) and levels of tryptophan hydroxylase 1 (TPH1), a rate-limiting enzyme in 5-HT biosynthesis, are elevated during pregnancy and lactation in mouse and bat mammary epithelial cells. 14,21) Fluoxetine, an SSRI that perturbs serotonin balance by binding to the serotonin reuptake transporter within mammary glands, inhibits β-casein expression in primary bovine mammary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%